Expressão do receptor de vitamina D recombinante: um importante alvo biológico - Thomaz, Aline Machado (2015)
The vitamin D receptor (VDR) is a cytoplasmic transcription factor and when activated by its ligand, translocates to the nucleus and interacts with DNA in the promoter regions with which has affinity, acting as a modulator of gene transcription and thereby producing multiple biological effects. Its main activities are the regulation and maintenance of plasma levels of calcium and phosphorus, as well as presenting immunomodulatory activities, such as the suppression of T cell activation, formation of secretion patterns of cytokines, modulation of proliferation and interference in the apoptosis. So this receptor is an important target for drugs that can help in the discovery of new immunomodulators. The present work had the objective to produce the recombinant vitamin D receptor in its soluble form for conducting future assays of drug screening of potential immunomodulators and drug-receptor interaction studies. For this, we used initially Escherichia coli expression system transformed with the plasmid HS_VDR_EC1-PQE T7, but it was only possible to obtain the protein in the insoluble fraction, even varying the temperature, time of induction and IPTG concentration. In an attempt to obtain soluble VDR, we used a eukaryotic expression system in insect cells using the baculovirus as a vector. It was built a vector, pFASTBacHT_VDR, which had the sequence of this protein cloned from pCMX.VDR. From there, it was possible to obtain recombinant bacmids used in transfection of insect cells, generating recombinant baculovirus, to then proceed with the expression of VDR.